THE INFLUENCE OF SERVICE QUALITY, PRODUCT VARIATION, AND LOCATION ON CUSTOMER SATISFACTION AT BAPADE'S COFFEE KEMANGGISAN, WEST JAKARTA - Andhika Yoga Pratama; Suadi Sapta Putra; Kumba Digdowiseiso (Jurnal Ekonomi, 2023)
This research aims to determine the influence of Service Quality, Product Variety, and Location on Customer Satisfaction at Bapades Coffee Kemanggisan, West Jakarta. The sample studied in this study amounted to 121 respondents, the data collection method used a questionnaire method with a Likert scale and the data analysis technique used Multiple Linear Analysis using the SPSS version 23 program. The results of the study had a regression equation Y = 0.616 X1 + 0.53 X2 + 0.192 X3 Based on the results of the T Test, it shows that there is an influence between Service Quality (X1) on Customer Satisfaction (Y) based on T count 6,949 > T table 1,660 and a sig value of 0.000 < 0.50. The Product Variation variable (X2) does not have a significant influence on Customer Satisfaction (Y) based on T count 0.738 < 1,660 T table and sig value 0.462 > 0.50. For the Location variable (X3), it shows that there is an influence on Customer Satisfaction (Y) based on the calculated T value of 2,183 > 1,660 T table and the sig value of 0.31 < 0.50. The results of this research conclude that the variables Service Quality and Location have a significant influence on Customer Satisfaction. Another conclusion from this research is that product variety does not have a significant effect on customer satisfaction